2011
DOI: 10.1016/j.ccr.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Tumor Interactome Screen Reveals ER Stress Response Can Reprogram Resistant Cancers for Oncolytic Virus-Triggered Caspase-2 Cell Death

Abstract: To identify therapeutic opportunities for oncolytic viral therapy, we conducted genome-wide RNAi screens to search for host factors that modulate rhabdoviral oncolysis. Our screens uncovered the endoplasmic reticulum (ER) stress response pathways as important modulators of rhabdovirus-mediated cytotoxicity. Further investigation revealed an unconventional mechanism whereby ER stress response inhibition preconditioned cancer cells, which sensitized them to caspase-2-dependent apoptosis induced by a subsequent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 28 publications
(40 reference statements)
1
87
1
Order By: Relevance
“…6,17 The reliance on the joint induction of ROS and ER stress for the efficient emission of DAMPs is perhaps not surprising Abbreviations: ATP, adenosine triphosphate; CRT, calreticulin; DAMP, damage-associated molecular patterns; GRP, glucose-regulated protein; HMGB1, high mobility group box-1; HSP, heat shock protein; ICD, immunogenic cell death; PDT, photodynamic therapy; UVC, ultraviolet C a Oncolytic viruses can cause necrosis in cancer cells 119 as well as apoptosis. 120 Specifically, in the aforementioned study, the authors confirmed that CVB3-induced ICD was of apoptotic nature through analysis of phosphatidylserine externalization (in the absence/presence of permeabilization) and DNA fragmentation. 26 b It has to be considered that cyclophosphamide's effects on anti-tumour immunity are strongly dose-dependent.…”
Section: Er Stress and Ros: At The Origins Of Danger Signalling?supporting
confidence: 54%
“…6,17 The reliance on the joint induction of ROS and ER stress for the efficient emission of DAMPs is perhaps not surprising Abbreviations: ATP, adenosine triphosphate; CRT, calreticulin; DAMP, damage-associated molecular patterns; GRP, glucose-regulated protein; HMGB1, high mobility group box-1; HSP, heat shock protein; ICD, immunogenic cell death; PDT, photodynamic therapy; UVC, ultraviolet C a Oncolytic viruses can cause necrosis in cancer cells 119 as well as apoptosis. 120 Specifically, in the aforementioned study, the authors confirmed that CVB3-induced ICD was of apoptotic nature through analysis of phosphatidylserine externalization (in the absence/presence of permeabilization) and DNA fragmentation. 26 b It has to be considered that cyclophosphamide's effects on anti-tumour immunity are strongly dose-dependent.…”
Section: Er Stress and Ros: At The Origins Of Danger Signalling?supporting
confidence: 54%
“…The IRE1α/XBP1 pathway is often activated in cancers and has recently emerged as a potential molecular target for anticancer therapy (1,5,(39)(40)(41)(42)(43), especially for multiple myeloma, which is characterized by malignant plasma cells producing a high amount of immunoglobulin (26,42,44,45). These previous studies showed that the pharmacological inhibition of IRE1α endonuclease significantly suppressed myeloma tumor growth in a model of human malignant myeloma xenografts, corroborating the idea that the IRE1α/XBP1 pathway may serve as a promising molecular target.…”
Section: Discussionmentioning
confidence: 99%
“…Both viruses are known to induce a strong ER or unfolded protein stress response (UPR), which can lead to apoptosis (Mahoney et al, 2011). Interestingly, by keeping protein levels of RAIDD low, the ERstress response machinery appears to be able to delay caspase-2-dependent apoptosis upon infection (Mahoney et al, 2011).…”
Section: Modes Of Activationmentioning
confidence: 99%
“…Both viruses are known to induce a strong ER or unfolded protein stress response (UPR), which can lead to apoptosis (Mahoney et al, 2011). Interestingly, by keeping protein levels of RAIDD low, the ERstress response machinery appears to be able to delay caspase-2-dependent apoptosis upon infection (Mahoney et al, 2011). Under conditions of sustained ER stress, however, the ER stress response factor IRE1a (also known as ERN1), an ER transmembrane kinase-endoribonuclease (RNase), promotes the rapid degradation of microRNAs that target caspase-2 mRNA.…”
Section: Modes Of Activationmentioning
confidence: 99%